Reproductive Coercion and Intimate Partner Violence Victimization Among a Racially and Ethnically Diverse Young Adult Sample - Muñoz, Emily A. (Journal of interpersonal violence, 2023)
Reproductive coercion is an understudied form of intimate partner violence (IPV) that occurs when a person attempts to control the autonomous reproductive decision making of their intimate partner. Previous research has demonstrated that individuals who experience reproductive coercion are more likely to experience other forms of IPV (e.g., physical and sexual). Research has also shown that Black/African American and Latinx/Hispanic individuals are at an increased risk of experiencing reproductive coercion compared to their White/Non-Hispanic peers. However, most of the research on reproductive coercion has been conducted in family-planning clinics where IPV is reported at a higher rate than in community samples. Thus, using a diverse community sample of female-identifying young adults (N = 370) who were recruited as part of an ongoing longitudinal study on dating violence, we examined the prevalence of lifetime reproductive coercion and its relationship with other forms of IPV, as well as the differences in prevalence among racial and ethnic groups. Lifetime prevalence of being victimized by any form of reproductive coercion was 11.4%. Results indicated that individuals who experienced reproductive coercion were more likely to experience physical and sexual IPV relative to those who did not experience reproductive coercion. With respect to race/ethnicity, 5.6% of White participants, 10.5% of Black/African American participants, and 14.8% of Hispanic/Latinx participants reported experiencing reproductive coercion. Chi-square analyses showed Hispanic/Latinx participants had a significantly higher prevalence of reproductive coercion when compared to White/Non-Hispanic participants. These findings suggest a need for additional research on culturally-specific risk and protective factors related to reproductive coercion among Hispanic/Latinx individuals to identify potential intervention and prevention strategies.